Assessing Liver Function in Liver Tumors Patients: The Performance of T1 Mapping and Residual Liver Volume on Gd-EOBDTPA-Enhanced MRI - Duan, Ting; Jiang, Hanyu; Xia, Chunchao; Chen, Jie; Cao, Likunn; Ye, Zheng; Wei, Yi; Song, Bin; Lee, Jeong Min (Frontiers in Medicine, 2020)
Purpose: To assess the performance of T1 mapping and residual liver volume (RLV) on Gd-EOBDTPA-enhanced MRI in pretreatment estimation of liver function in patients with liver tumors. Indocyanine green retention rate at 15 min (ICG R-15) was used as a reference standard. Methods: Ethical approval from the institutional review board and informed consent were obtained for this prospective study. We enrolled 155 patients with liver tumors who underwent pretreatment Gd-EOB-DTPA-enhanced MRI. T1 relaxation time before (T1-pre), 20 min after (T1-post) Gd-EOB-DTPA injection and RLV were measured. The absolute reduction (ΔT1) and reduction rate (ΔT1%) of T1 relaxation time, volume-assisted ΔT1 (ΔT1*RLV) and volume-assisted ΔT1% (ΔT1%*RLV) were calculated accordingly. The correlation of MR parameters with ICG R-15 was determined using Spearman’s rank correlation analysis. Patients were classified into the normal liver function (NLF) group if their ICG R-15 levels were less than 10% or otherwise into the abnormal liver function (ALF) group. Receiver operating characteristic (ROC) analysis was conducted to evaluate the performances of the MR parameters in predicting ALF. Results: T1-post (r=0.472, P<0.001), ΔT1 (r=-0.355, P=0.011), ΔT1% (r=-0.482, P<0.001), RLV (r=-0.336, P<0.001), volume-assisted ΔT1 (r=-0.458, P<0.001) and volume-assisted ΔT1% (r=-0.522, P<0.001) showed weak to moderate correlation with ICG R-15. The area under the ROC curves (AUROC) of volume-assisted ΔT1 in predicting ALF was 0.777, which was significantly higher than the other parameters (P<0.05 for all). Conclusions: Combined T1 mapping and RLV on Gd-EOB-DTPA-enhanced MRI can help assess liver function with good diagnostic accuracy in patients with liver tumors before treatment.